Shafting Alignment Based on Hydrodynamics Simulation Under Larger Rudder Corner Conditions - 杨勇 马捷 唐文勇 车驰东 张桂臣 (Shanghai jiao tong da xue xue bao, 2012)
With the rudder angles getting larger and larger, the moment and force on propeller shafts, which are caused by complex flowing field, become more and more. They influence the shafting alignment greatly. Stress analysis of propeller shafts has been done under increasing rudder corner conditions with complex hydrodynamics simulation for a great domestic liquified natural gas （LNG） vessel, which is with dual propulsion systems. The improved three-moment equation is adopted in the process of dual propulsive shafting alignment. The calculated results show that the propeller hydrodynamic characteristics, which affect dual propulsive shafting alignment greatly, must be considered under large rudder angle conditions. Shafting accidents of Korean LNG vessels are interpreted reasonably. At the same time, salutary lessons and references are afforded to the marine multi-propulsion shaftin alignment in the future.